(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2025)
This thesis investigates literary aphorisms as stylistic devices for foregrounding in texts. Foregrounding, a key concept in stylistics, involves the deliberate deviation from linguistic norms to create emphasis, draw attention, or enhance aesthetic effect. Literary aphorisms, with their concise, striking, and often paradoxical nature, serve as effective tools for foregrounding key ideas, themes, and conceptual insights. The study analyzes the structural and semantic strategies that contribute to the prominence of aphoristic expressions, exploring how authors employ them to highlight philosophical, moral, and cognitive content. The research demonstrates that aphorisms not only enrich literary style but also guide readers’ attention and interpretation, thereby playing a significant role in textual meaning-making.